National Policy and Strategies (NPS) Coordination team holds 1st Hackathon in Kenya - CGIAR Initiative on National Policies and Strategies (CGIAR System Organization, 2023)
International Water Institute (IWMI) and CGIAR Initiative on National Policies and Strategies, through its Coordination team together with Wetlands International, held the 1st ever Water Policy Hackathon in Nairobi, Kenya, for the youth and key stakeholders in the water sector from the 18th-19th May 2023. The Engagement had over 35 stakeholders from Civil Society Organizations, representatives from the different government ministries in Kenya, and key youth players in the water sector.